IMPLEMENTAÇÃO DE UM SIMULADOR NUMÉRICO EM UM PROGRAMA COMPUTACIONAL DE ESTABILIDADE - Paz, Alex Ricardo Arquiñego (2004)
The main objective of this research is to implement and evaluate the performance of a numerical solver known as DASSL, in a transient and long-term stability program, applied in the solution of differential and algebraic equations representing the network and its components. The solver is a computer code purely mathematic, ready to use, comprising numerical methods suitable to the analysis of interested phenomena. The user must develop an interface to the input and output data according to his personal interests, i.e., according to the problem being solved. The solver efficiency was tested in several steps. The beginning was over the solution of a first order ordinary differential equation, moving to computer tests with hypothetical power systems, increasing gradatively the computer simulation complexity. The obtained results revealed that this solver is very efficient in time domain transient and long-term stability studies, certifying that the power system dimension is either small- or medium-port. The resulting information from this work form the basis to the implementation of advanced solvers in a stability program. The goal is, independently of the power system size, provide a small processing time keeping the reliability of the numerical results.